Chemical inhibitors of CYP450 enzymes in liver microsomes: combining selectivity and unbound fractions to guide selection of appropriate concentration in phenotyping assays. (February 2015) - Nirogi, Ramakrishna; Palacharla, Raghava Choudary; Uthukam, Venkatesham; Manoharan, Arunkumar; Srikakolapu, Surya Rao; Kalaikadhiban, Ilayaraja; Boggavarapu, Rajesh Kumar; Ponnamaneni, Ranjith Kumar; Ajjala, Devender Reddy; Bhyrapuneni, Gopinadh
Abstract 1. Chemical inhibition is the widely used method in reaction phenotyping assays for estimation of specific enzyme contribution to a given metabolic pathway. The results from phenotyping assays depend on the selectivity of chemical inhibitor and the concentration of inhibitor used in the incubation. 2. The higher protein concentrations used in the in vitro phenotyping assays will impact the inhibitory potency of chemical inhibitors. The objective of the study is to evaluate comprehensively the selectivity of chemical inhibitors and to guide in selecting appropriate concentration of the chemical inhibitors to be used in the phenotyping assays based on unbound fractions. 3. Selectivity of chemical inhibitors against nine major CYP450 isoforms was determined in liver microsomes using standard probe substrates. The unbound fractions of the selective inhibitors were determined in human liver microsomes using high-throughput equilibrium dialysis. Combining unbound inhibitor concentrations that are required to inhibit the CYP450 activities by 90% and unbound fractions of the chemical inhibitors in liver microsomes appropriate total concentrations of the inhibitors to be used in the phenotyping assays were reported. 4. The findings suggest that non-specific binding of the chemical inhibitors need to be taken into account while selecting concentrations for phenotyping assays.